Sueño Bay adventures. 3, Hermit Hill - Deas, Mike, 1982-; Deas, Nancy (Deas, Mike, 1982- Sueño Bay adventures, 2022)
"In this graphic novel for early middle readers, the youngest member of a ragtag crew of kids feels left out of a big project and finds himself a group of magical Moon Creatures to lord over"--Provided by publisher.